Peran Organisasi-Organisasi Kemasyarakatan Islam dalam Pemberdayaan Penyandang Disabilitas di Kota Surakarta - Luthfiyah Trini Hastuti; Burhanudin Harahap; Agus Rianto; Nur Sulistyaningsih (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Discriminatory behavior experienced by persons with disabilities is still often encountered, one of which is access to job opportunities. The cause of the low access to work is due to the low access to education of persons with disabilities. This study aims to describe the role of Islamic Community Organizations in Surakarta City as a strategic entity partnering the government in solving problems experienced by people with disabilities. The theory used refers to the theory of Human Rights in the Islamic concept. In essence, Islam provides equality to all people in obtaining education, employment, and other rights which are summarized in the five basic needs. This research is a non-doctrinal legal research. The data used are the results of interviews conducted with the management of NU and Muhammadiyah in the city of Surakarta. Data analysis was carried out using material logic with an inductive syllogism. The results showed that the role of Islamic organizations NU and Muhammadiyah in Surakarta in the field of education has been realized. The inclusive education program through SMA Muhammadiyah 6 Surakarta and inclusive madrasah which are currently managed by Islamic organizations are trying to improve the quality of life for people with disabilities. Another role that can be carried out is in the field of religion by providing worship facilities and developing fiqh with disabilities. In the field of economic empowerment, Islamic organizations NU and Muhammadiyah have experience in managing social funds sourced from zakat, infaq, and shodaqoh. The management of community social funds can be expanded to provide benefits for persons with disabilities in the form of working capital assistance.